2004
DOI: 10.1177/0146167204271185
|View full text |Cite
|
Sign up to set email alerts
|

Ageism and Death: Effects of Mortality Salience and Perceived Similarity to Elders on Reactions to Elderly People

Abstract: The present research investigated the hypotheses that elderly people can be reminders of our mortality and that concerns about our own mortality can therefore instigate ageism. In Study 1, college-age participants who saw photos of two elderly people subsequently showed more death accessibility than participants who saw photos of only younger people. In Study 2, making mortality salient for participants increased distancing from the average elderly person and decreased perceptions that the average elderly pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 48 publications
(49 reference statements)
8
114
0
2
Order By: Relevance
“…Studies have also shed light on the mechanisms that lead from mortality salience to in-group bias, indicating the mediating role of in-group identification and perceived collective continuity (Castano et al 2002;Herrera and Sani 2013) as well as control motivation (Agroskin and Jonas 2013). In addition, studies have found that mortality salience increased the use of stereotypes based on nationality, race, gender, sexual orientation, and age (e.g., Castano 2004;Martens et al 2004;Schimel et al 1999). The use of negative stereotypes further increased when a competitive or threatening out-group member was present (Renkema et al 2008).…”
Section: Social Groups and Stereotypes In Light Of Terror Management mentioning
confidence: 99%
“…Studies have also shed light on the mechanisms that lead from mortality salience to in-group bias, indicating the mediating role of in-group identification and perceived collective continuity (Castano et al 2002;Herrera and Sani 2013) as well as control motivation (Agroskin and Jonas 2013). In addition, studies have found that mortality salience increased the use of stereotypes based on nationality, race, gender, sexual orientation, and age (e.g., Castano 2004;Martens et al 2004;Schimel et al 1999). The use of negative stereotypes further increased when a competitive or threatening out-group member was present (Renkema et al 2008).…”
Section: Social Groups and Stereotypes In Light Of Terror Management mentioning
confidence: 99%
“…This measure consisted of a single item asking participants to "Please rate how similar/different you think you are to small insects" on a 9-point bipolar scale ranging from not at all similar (1) to extremely similar (9). A similar question was used successfully in past research also investigating the threatening implications of similarity (Martens et al, 2004). The experimenter was blind to these ratings.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Greenberg et al . (2002) proposed that individuals cope with the anxiety induced by such threats by denigrating entities that serve as reminders of their own fate (see also Martens, Greenberg, Schimel, & Landau, 2004; Nelson, 2005). Consistent with this reasoning, several studies have found a positive correlation between ageing anxiety and ageism (Allan & Johnson, 2009; Allan, Johnson, & Emerson, 2014; Boswell, 2012; Harris & Dollinger, 2001).…”
Section: Introductionmentioning
confidence: 99%